EVALUATION OF THE HABIT OF READING NUTRITION LABELS IN CONSUMERS: CASE OF ELAZIĞ CITY - Kurt, Osman; Pirincci, Edibe; Çimen, Elifnur; Balalan, Edanur; Akgün, Özge; Oguzoncul, Ayse Ferdane; Deveci, Süleyman Erhan (My University, 2022)
This study, it was aimed to evaluate the nutrition label reading habits of adult consumers aged 18 and over, in Elazığ city center. This cross-sectional study consists of consumers who shop from the shopping malls in Elazığ city center. 300 people were reached in the study. Evaluating the “always” response as 2 points, “sometimes” as 1 point, and the “never” as 0 points, the “Nutrition Label Reading Habit Score” was obtained. The score that can be obtained varies between 0 and 56. While 28% of the participants “always” read the nutrition label, 62% “sometimes”, and 10% “never” read it. The mean score for the nutrition label reading habit of women was significantly higher than that of men (p=0.002). Among the age groups, the highest score was significantly in the 35-44 age group (p=0.004). As the education level increased, the score also increased considerably (p<0.001). The score was found to be notably higher in consumers who are working, married, and have children (p<0.05). The scores of those who received nutrition training than those who did not receive such education (p<0.001), and scores of those who read the nutrition label while using the product instead of reading it at home were significantly higher (p=0.002). It has been observed that there are deficiencies in reading the nutrition labels on packaged products, at the same time; women, those with a high level of education, those who are married, have children, and those who have received nutritional education have a higher habit of reading nutrition labels.
Keywords: Consumer behaviour; Consumer; nutrition label